How internal attributions affect knowledge sharing behavior. Issue 4 (13th February 2018) - Lekhawipat, Watcharee; Wei, Yu-Huei; Lin, Chinho
Abstract : Purpose: The purpose of this paper is to compare the effects of organizational and technological barriers to knowledge sharing between large and small firms through the lens of attribution theory. Design/methodology/approach: The structural equation modeling approach was applied to estimate the conceptual model by using survey data from a list of Taiwan's top 1, 000 manufacturing and 500 service companies. A total of 229 valid questionnaires were collected. Findings: The empirical results show that both organizational and technological barriers have relationships with an individual's effort and ability with regard to knowledge sharing behavior. When organizational barriers occur, the perceived lack of effort has a direct effect on knowledge sharing behavior for large firms, while negative sharing behavior among employees of small firms is influenced by the perception of low ability through the perceived lack of effort. Originality/value: A review of the literature reveals organizational and technological barriers that lead to the negative influences of internal attributions on knowledge sharing. This study, therefore, contributes to a comprehensive perspective on how to encourage knowledge sharing behavior at different sizes of firms.